2001
DOI: 10.1002/jctb.364
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fermentation parameters on the production of Mucor miehei acid protease in a chemically defined medium

Abstract: Batch shake flask experiments were carried out with a fungal strain of Mucor miehei ATCC 3420 to study the effects of five fermentation parameters; initial D‐glucose concentration, temperature, initial pH, agitation rate and inoculum ratio, on the production of rennin in a chemically defined medium. A statistical design was used to assign the experimental levels of five fermentation parameters for the determination of optimum conditions. The highest concentration of milk‐clotting activity (MCA) obtained was 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Finally, this is one of the few studies carried out for studying the influence of production parameters on increasing milk-clotting production through statistical methods and in SSF or biphasic systems. To the best of the authors' knowledge, the only reference to the use of statistical design for mcp production has been reported by Ayhan et al [13] for Mucor sp.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Finally, this is one of the few studies carried out for studying the influence of production parameters on increasing milk-clotting production through statistical methods and in SSF or biphasic systems. To the best of the authors' knowledge, the only reference to the use of statistical design for mcp production has been reported by Ayhan et al [13] for Mucor sp.…”
Section: Discussionmentioning
confidence: 95%
“…4). On the contrary, Ayhan et al [13] have reported using 5.2% (v/v) of inoculum for Fig. 4 Effect of different moistening agents on mcp production in SSF Fig.…”
Section: Production Under Submerged Fermentation Using Response Surfamentioning
confidence: 96%
“…Various animals, plants and microbial proteases have been suggested as milk coagulants (Chazarra et al 2007 ; D’Ambrosio et al 2003 ; Silva & Malcata 2005 ; Zhang et al 2011 ). However, attention has been focused on the production of milk-clotting enzymes (MCEs) from microbial sources for use as rennin substitutes (Ayhan et al 2001 ; Cavalcanti et al 2004 ; Hashem 1999 ; Silveira et al 2005 ). Although there are many microorganisms that produce MCEs (Ding et al 2011 ; He et al 2011 ; Li et al 2012 ; Vishwanatha et al 2010 ), only the MCEs produced by strains of Rhizomucor miehei , Rhizomucor pusillus var.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works on the optimization of parameters for MCE production were conducted using " one-factor-at -a-time" technique (Ayhan et al 2001 ; Cavalcanti et al 2004 ; Hashem 1999 ; Silveira et al 2005 ). Unfortunately, it frequently fails to locate the region of optimum response because the joint effects of factors on the response are not taken into account in such procedure.…”
Section: Introductionmentioning
confidence: 99%
“…being marketed since the 1970s have proved satisfactory for the production of different kinds of cheese. The molecular and enzymatic properties of chymosins have been studied extensively (Jonk and Birkkjacer, 1985;Crawford, 1985;Ayhan et al, 2001).In this study the production conditions of milk clotting enzyme from new strain Streptomyces pseudogrisiolus NRC 15 were optimized. In addation the milk clotting enzyme was also purified and characterized.…”
mentioning
confidence: 99%